Reading financial reports for dummies - Epstein, Lita (Gildan Audio, 2019)
Discover how to decipher financial reports Especially relevant in today's world of corporate scandals and new accounting laws, the numbers in a financial report contain vitally important information about where a company has been and where it is going. Packed with new and updated information, Reading Financial Reports For Dummies, 3rd Edition gives you a quick but clear introduction to financial reports-and how to decipher the information in them. - New information on the separate accounting and financial reporting standards for private/small businesses versus public/large businesses - New content to match SEC and other governmental regulatory changes - New information about how the analyst-corporate connection has actually changed the playing field - The impact of corporate communications and new technologies - New examples that reflect current trends Reading Financial Reports For Dummies is for investors, traders, brokers, managers, and anyone else who is looking for a reliable, up-to-date guide to reading financial reports effectively.